Parallel Algorithm For Sorting Animal Pedigrees - Maciej Gierdziewicz (Computer Science, 2009)
In many analyses of animal genotype with the methods of quantitative genetics there is a needto account for relationships among individuals. Incorrectly calculated relationship coefficientsmay lead to biased estimates. The number of software packages exist which deal with thatproblem; however, in many of them it is assumed that pedigrees of the individuals are sortedchronologically, but in real data sets – containing information on traits and pedigrees – birthdates are often missing. In extreme cases, when (almost) no birth dates are present, theordering must be made by comparing – at least once – each pair of individuals separately,since it is not sufficient to compare adjacent elements in order to check whether the dataset is sorted. Two versions of parallel computer programs were compared, with constant orvariable distance between elements of compared pairs. The results indicate that the secondalgorithm is more efficient.